16.3k views
0 votes
Which of the following is an equivalent expression for tan to the power of minus 1 end exponent x plus tan to the power of minus 1 end exponent left parenthesis minus x right parenthesis

tan^-1x+tan^-1(-x)

a. -1

b. rad

c. 0

d. rad/2

e. 1

User Dnuttle
by
5.8k points

1 Answer

2 votes

Answer:

c)

Explanation:

To solve this, remember some properties of trigonometric functions.

Let
y=\tan^(-1) (x). Then, by definition of inverse function,
\tan(y)=x. Multiply by -1 to both sides of this equation to get
-\tan(y)=-x.

Note that
-\tan(y)=(-\sin(y))/(\cos(y))=(\sin(-y))/(\cos(y))=(\sin(-y))/(\cos(-y))=\tan(-y) because sine is an odd function and cosine is an even function. Then
\tan(-y)=-x. Take the inverse tangent in both sides to get
-y=\tan^(-1) (-x).

Using the previous equations, we obtain:


\tan^(-1) (x)+\tan^(-1) (-x)=y+(-y)=0

User Gordonium
by
5.6k points